RESPON VARIETAS PADI UNGGUL KETAN KUTUK PADA BEBERAPA FORMULASI PEMUPUKAN NPK TERHADAP PRODUKTIFITAS - Suharno, Suharno (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2015)
Research conducted on the characteristics of the land soil type Regosol, sand texture argillaceous, a height of 114 m above sea level, the type of wetland with cropping pattern of paddy-rice-crops, irrigation systems semi technical, in the planting season 3, the former rice plant gadu, in the village of Sumberharjo districts Prambanan special region of Yogyakarta Sleman district. A study in May 2013 in November 2013. Methods Complete Randomized Block (RCBD), 3 NPK treatment, repent 6 times, 18 plots, a plot area of 1000 m2. Materials used three types of fertilizer NPK (Formula I: Phonska; Formula II: Pearls; Formula III : Tablets ), Ketan Kutuk rice seed Local superior. Implementation of research, planting mode SRI, cropping system tiles, a dislance of 20 x 20 cm, fertilization principled 4 ringh (type, dose, method, tame). Basic fertilization: before planting time, type of super petroganik 640 kg, 10 kg ZA, distributed way. Fertilization aftershocks 1 : 21 days, the type and dose of fertilizer every 4 clumps that (Phonska 5 grams; 5 grams of Pearl; and Tablets 2 point (5 grams), means embedded in the soil. Fertilization aftershocks 2 = age 40 days after planting, the type and dose of Urea 10 kg, carat deployed. Plant maintenance according per formed by local farmers. The results showed that treatment types of NPK 3 formula (Phonska, Pearls, Tablets) no real effect on plant height, weight of wet hay, straw dry weight, weight of 1000 grains, number of grains per panicle, and the weight of dry milled grain. Real effect and significant fly different DMRT 5 % treatment types of NPK fertilizer to the number of productive tillers. Local superior rice Ketan Kutuk to respond to various types of NPK 3 formula (Phonska, Pearl, Tablets) with productivity (4,275 ton/ha; 5,5 tons/hectare; and 4,140 tonnes/hectare)